Disease-Specific Contribution of Pulvinar Dysfunction to Impaired Emotion Recognition in Schizophrenia - Martínez, Antígona; Tobe, Russell H.; Gaspar, Pablo A.; Malinsky, Daniel; Dias, Elisa C.; Sehatpour, Pejman; Lakatos, Peter; Patel, Gaurav H.; Bermudez, Dalton H.; Silipo, Gail; Javitt, Daniel C. (Frontiers in Behavioral Neuroscience, 2022)
One important aspect for managing social interactions is the ability to perceive and respond to facial expressions rapidly and accurately. This ability is highly dependent upon intact processing within both cortical and subcortical components of the early visual pathways. Social cognitive deficits, including face emotion recognition (FER) deficits, are characteristic of several neuropsychiatric disorders including schizophrenia (Sz) and autism spectrum disorders (ASD). Here, we investigated potential visual sensory contributions to FER deficits in Sz (n = 28, 8/20 female/male; age 21–54 years) and adult ASD (n = 20, 4/16 female/male; age 19–43 years) participants compared to neurotypical (n = 30, 8/22 female/male; age 19–54 years) controls using task-based fMRI during an implicit static/dynamic FER task. Compared to neurotypical controls, both Sz (d = 1.97) and ASD (d = 1.13) participants had significantly lower FER scores which interrelated with diminished activation of the superior temporal sulcus (STS). In Sz, STS deficits were predicted by reduced activation of early visual regions (d = 0.85, p = 0.002) and of the pulvinar nucleus of the thalamus (d = 0.44, p = 0.042), along with impaired cortico-pulvinar interaction. By contrast, ASD participants showed patterns of increased early visual cortical (d = 1.03, p = 0.001) and pulvinar (d = 0.71, p = 0.015) activation. Large effect-size structural and histological abnormalities of pulvinar have previously been documented in Sz. Moreover, we have recently demonstrated impaired pulvinar activation to simple visual stimuli in Sz. Here, we provide the first demonstration of a disease-specific contribution of impaired pulvinar activation to social cognitive impairment in Sz.